Electronic Commerce A Managerial and Social Networks Perspective - Turban, Efraim. (Springer Texts in Business and Economics,, 2015)
Throughout the book, theoretical foundations necessary for understanding Electronic Commerce (EC) are presented, ranging from consumer behavior to the economic theory of competition. Furthermore, this book presents the most current topics relating to EC as described by a diversified team of experts in a variety of fields, including a senior vice president of an e-commerce-related company. The authors provide website resources, numerous exercises, and extensive references to supplement the theoretical presentations. At the end of each chapter, a list of online resources with links to the websites is also provided. Additionally, extensive, vivid examples from large corporations, small businesses from different industries, and services, governments, and nonprofit agencies from all over the world make concepts come alive in Electronic Commerce. These examples, which were collected by both academicians and practitioners, show the reader the capabilities of EC, its cost and justification, and the innovative ways corporations are using EC in their operations. In this edition (previous editions published by Pearson/Prentice Hall), the authors bring forth the latest trends in e-commerce, including social businesses, social networking, social collaboration, innovations, and mobility.